Eficacia de la ketamina para la prevención de temblores postoperatorios en pacientes sometidos a anestesia general - Alcántara Trujillo, Marcos Jonathan (2019)
Introduction: Postanesthetic tremor is an involuntary movement that affects one or several muscle groups, which usually occurs in the first phase of recovery after general anesthesia. According to multiple reviews, the incidence fluctuates between 6 and 66%; Gender (predominantly in men) and surgery time seem to be the determining factors for postanesthetic tremor. There are few reports on the usefulness of ketamine for the prevention of postoperative tremors. Emine and cols established the efficacy of two doses of ketamine compared to meperidine for the treatment of postoperative chills. Objective: To evaluate the effectiveness of ketamine in the prevention of postoperative tremors in patients undergoing general anesthesia. Method: This study corresponds to a prospective cohort design